2019
DOI: 10.1053/j.gastro.2019.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis D Virus-Specific CD8+ T Cells Have a Memory-Like Phenotype Associated With Viral Immune Escape in Patients With Chronic Hepatitis D Virus Infection

Abstract: Background & Aim: Hepatitis D virus (HDV) superinfection of patients with chronic HBV infection results in rapid progression to liver cirrhosis. Little is known about HDV-specific T cells and how they contribute to the anti-virus immune response and liver disease pathogenesis. Methods: We isolated peripheral blood mononuclear cells from 28 patients with chronic HDV and HBV infection, identified HDV-specific CD8 + T-cell epitopes and characterized HDV-specific CD8 + T cells. We associated these with HDV sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(91 citation statements)
references
References 33 publications
2
89
0
Order By: Relevance
“…Our results contradict recent publications suggesting a role for HDV-specific CD8+ T cells in HDV-induced liver pathology. 13,14 Kefalakes et al showed a very weak positive correlation between AST levels and activated HDV-specific CD8+ T cells in circulation in a small number of chronically HDV-infected patients. However, circulating T cells might not reflect what is happening in the liver, and the cytolytic capacity of these cells has yet to be characterized.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results contradict recent publications suggesting a role for HDV-specific CD8+ T cells in HDV-induced liver pathology. 13,14 Kefalakes et al showed a very weak positive correlation between AST levels and activated HDV-specific CD8+ T cells in circulation in a small number of chronically HDV-infected patients. However, circulating T cells might not reflect what is happening in the liver, and the cytolytic capacity of these cells has yet to be characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in accordance with the weak adaptive immune response against HDV antigens and the dysfunctionality of innate immune cells (such as NK and MAIT cells) that has been observed in HDV-infected patients. [10][11][12][13][14] It is known for some individuals that a strong innate immune response against a viral infection can lead to tissue damage and chronic disease rather than to viral clearance, as in the case of HCV. [31][32][33] The transcriptomic analysis of the liver in our model revealed a strong induction of pathways activated by IFN-c and TNF-a in AAV-HBV/HDV-in comparison to AAV-HBV-treated animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the setting of chronic lymphocytic choriomeningitis (LCMV) infection in mice, TCF-1 marks the subpopulation of stem-like virus-specific CD8+ T cells that is capable of regenerating both the ongoing effector cell response as well as the proliferative burst of effector cells that is observed after blockade of the PD-1 signaling pathway (36)(37)(38). In humans, expression of TCF-1 in subpopulations of virus-specific CD8+ T cells has been reported in individuals chronically 6 infected with hepatitis B virus (HBV) (39), hepatitis D virus (HDV) (40), or Epstein-Barr virus (EBV) (40), and TCF-1 expression has been correlated with virus-specific T cell expansion capacity in the context of infection with hepatitis C virus (HCV) (37,41). Furthermore, in several recent clinical trials of individuals with melanoma, the size of the TCF-1-expressing subpopulation of intra-tumoral CD8+ T cells was strongly correlated with the clinical response to checkpoint blockade therapy (42,43).…”
Section: Introductionmentioning
confidence: 99%